SMEs' responses to potentially disruptive innovations: Does strategic entrepreneurship provide an explanation? - Rosemarie Kay; Sebastian Nielen; Christian Schröder (Institut für Mittelstandsforschung (IfM) Bonn, 2018)
This study analyses how established SMEs respond to potentially disruptive inno-vations and business models in the course of increasing digitization. Drawing on the strategic entrepreneurship approach we argue that SMEs showing strategic entrepreneurial behaviour are more likely to respond to potentially disruptive innovations and business models proactively. We find that established SMEs recognizing disruptive innovations and business models as a business opportunity apply significantly more frequently strategic measures to exploit these opportunities. Observing and evaluating relevant new technologies and devel-opments is a key determinant of belonging to the group of SMEs demonstrating strategic en-trepreneurial behaviour. In our sample only a minority belongs to the group of proactive es-tablished SMEs.
Keywords: L26; L21; M21; 330; SMEs; Strategic Entrepreneurship; Digitization; Disruptive Innovations; New Business Models